Manajemen Pengadaan Bahan Baku Tebu di Pabrik Gula Madukismo Daerah Istimewa Yogyakarta - Kiki Windian; Ernes Septina Azizi; Jefri Jitron Karmau (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
Sugarcane plays crucial and strategic role in the economy as the primary raw material for sugar production, thus ensuring proper procurement of sugarcane in the production process is crucial for smooth and successful production. This study aims to determine the management of sugarcane procurement and the constraints faced in meeting the demand for sugarcane at the Madukismo Sugar Factory in the Special Region of Yogyakarta. The basic method is descriptive. The location was determined intentionally at the Madukismo Sugar Factory in the Special Region of Yogyakarta, research was conducted from December 22, 2021, to January 15, 2022. The sampling technique was purposive sampling. Data collection methods included observation, interviews, and recording. The data analysis method was descriptive. The results of the study indicate that the procurement mechanisms for sugarcane include: factory capacity, planting area, planting schedule, and cutting schedule. Sugarcane planting is carried out in stages, starting from May to December, through partnership plantations and smallholder plantations. Harvesting and delivery of sugarcane to the Madukismo Sugar Factory are carried out in stages to prevent stockpiling of raw materials. Cutting is scheduled according to the harvest schedule, as the sugarcane harvest period is 12 months. Excess sugarcane raw materials at the Madukismo sugar factory will be processed the following day. Obstacles affecting the procurement of sugarcane raw materials at the Madukismo sugar factory include cutting labor, transportation, and the COVID-19 pandemic, which caused difficulties providing harvesting labor, resulting in delayed raw material delivery to the sugar factory in 2020 and 2021.